A risk assessment framework for alternative investment funds, both at fund level and market level - Iulian Panait; Paul Barangă (Financial Studies, 2018)
In this paper we propose an integrated approach to assessing risk for alternative investment funds, both at micro and macro (market) level. Building upon the experience and practice in European Supervisory Agencies and different National Competent Authorities on assessing risk for other type of financial intermediaries (ex. banks, insurance companies), we construct a risk dashboard for Alternative Investment Funds. Our proposed framework includes multiple categories of indicators and has both a time series approach and a cross sectional approach. At the same time, the proposed risk scoring can be calibrated using mechanically computed thresholds and expert judgment, in different combinations. The result is a new and flexible framework that can accommodate situations when not enough observations are available in the time series to compute mechanically the risk scores. In addition, it serves asset managers for their mandatory self-assessments and market supervisors in making relevant comparisons between the industry participants.
Keywords: G15; G23; G28; 330; risk dashboard; alternative investment funds; prudential supervision